Seeding fiber amplifiers with piecewise parabolic phase modulation for high SBS thresholds and compact spectra - White, Jeffrey O.; Young, Joshua T.; Wei, Chengli; Hu, Jonathan; Menyuk, Curtis (Optica, 2019)
We propose using piecewise parabolic phase modulation of the seed laser for suppressing stimulated Brillouin scattering (SBS) in a fiber amplifier. Simulations are run with a 9 m passive fiber. Compared with random phase modulation and 0-π pseudo-random phase modulation, the piecewise parabolic phase waveform yields a higher SBS threshold per unit bandwidth. If the bandwidth is defined as the range of frequencies containing 85% of the total power, the threshold for parabolic phase modulation is 1.4 times higher than the threshold for the five- or seven-bit pseudo-random modulation format. If the bandwidth is defined more tightly, e.g., the range of frequencies containing 95% of the total power, the threshold for parabolic phase modulation is three times higher. For both cases, achieving a bandwidth of 1.5 GHz requires a maximum phase shift of ~30 radians. All of the waveforms are compared on the basis of the bandwidth required of the phase moduator. The coherence functions are calculated in order to compare their suitability for coherent combining.
Keywords: Phase modulation; Phase shift; Laser beams; Brillouin scattering; Fourier transforms; UMBC Optical Fiber Communications Laboratory; Frequency modulation